(untitled) (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2022)
In this introduction to the first volume of the sixth issue of Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, we reflect on our experiences as members of the Editorial Team, advocate for the relevancy of graduate student journals, and introduce the three articles featured in this issue.